Penerapan Metode Polya dalam Pembelajaran Matematika untuk Meningkatkan Kemampuan Siswa dalam Menyelesaikan Masalah Matematika pada Materi Pecahan Kelas V di SDN Antirogo 01 Jember - Nuriani Dewi Novianti; N Nuriman; Erfan Yudianto (Jurnal Ilmu Pendidikan Sekolah Dasar, 2022)
Mathematics can develop students' abilities in finding, analyzing, and solving problems. Problem solving in mathematics is usually found by students in everyday life. Problems related to fraction material are often encountered by students in buying and selling activities. Fractions are a difficult material for elementary school students, especially to solve problems associated with fractional material. Ways or methods that students can use in solving problems in learning mathematics can use the Polya method. The Polya method is one method that students can use to solve problems, but there are still many students who do not know how to solve problems so that students' ability to solve problems can be said to be low. This study aims to improve students' ability to solve mathematical problems in fractions using the Polya method. The method used in this study is the classroom research method (CAR) which consists of 2 cycles with 4 stages in each cycle. The stages of each cycle are planning, implementation, observation, and reflection. Data were collected by giving a test to the research sample at the end of each cycle. The research is said to be successful if the average value of the class has increased. The results showed that the average grade of the students in the first cycle was 37 and in the second cycle it was 65.7. Based on the research results that have been described, this study has achieved its goal, namely the Polya method can improve students' ability to solve math problems in class V fractions at SDN Antirogo 01 Jember.